2022
DOI: 10.1155/2022/5315619
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effect of Catgut Embedding plus Warm Needle Moxibustion on Improving Inflammation and Quality of Life of Knee Osteoarthritis Patients

Abstract: Objective. To clarify influence of catgut embedding plus warm needle moxibustion on improving inflammation and quality of life of knee osteoarthritis patients. Materials and Methods. The data of 120 patients with knee osteoarthritis admitted to our hospital from June 2018 to June 2021 were used for retrospective analysis. Patients were divided into control group and observation group in a random manner, with 60 cases each. The control group was orally administrated with one diclofenac sodium sustained-release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Acupuncture is a minimally invasive, convenient, and feasible novel therapy. A large number of studies have confirmed that acupuncture can significantly inhibit the inflammatory response of the body [ 5 , 6 ], and has protective effects on nerve cells [ 7 ]. Transcutaneous electrical acupuncture (TEAS) is a non-invasive and simple alternative to acupuncture, combining the advantages of acupuncture and acupuncture with percutaneous electrical nerve stimulation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture is a minimally invasive, convenient, and feasible novel therapy. A large number of studies have confirmed that acupuncture can significantly inhibit the inflammatory response of the body [ 5 , 6 ], and has protective effects on nerve cells [ 7 ]. Transcutaneous electrical acupuncture (TEAS) is a non-invasive and simple alternative to acupuncture, combining the advantages of acupuncture and acupuncture with percutaneous electrical nerve stimulation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many clinical treatment options for KOA, including weight loss, exercise, painkillers, intra-articular hyaluronic acid, and joint replacement surgery[ 9 ]. Weight loss is mainly applicable to obese patients, while analgesics, intra-articular hyaluronic acid, and joint replacement surgery carry certain medication or surgical risks, especially for elderly patients with serious diseases[ 10 ]. Therefore, this study included an in-depth exploration of therapeutic strategies for KOA patients from the perspective of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%